2018
DOI: 10.1111/jan.13882
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model for fall risk in hospitalized adults: A case–control study

Abstract: Aim:To develop and validate a predictive model for falls in hospitalized adult clinical and surgical patients, assessing intrinsic (i.e. patient-related) and extrinsic factors (i.e. care process-related). Background:To identify factors predictive of falls and enable appropriate management of fall risk it is necessary to understand patient and environmental factors, along with care delivery processes. Design:A matched case-control study. Methods:This study was conducted in the medical and surgical wards of a Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 33 publications
1
10
0
16
Order By: Relevance
“…The analysis of the intervention by logistic regression revealed that a lower likelihood of falls in the intervention group was associated effectively with the method of care in the units included in this group, with no other studied variables being relevant. Our results are consistent with other studies that advocate for the benefits of using scales to identify the risk of falls [ 3 , 13 , 15 , 16 , 20 , 21 , 22 ]. Likewise, the systematic review by Miake-Lye et al [ 19 ] expresses the benefits of programs that include interventions to identify risk factors associated with falls in acute care environments.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The analysis of the intervention by logistic regression revealed that a lower likelihood of falls in the intervention group was associated effectively with the method of care in the units included in this group, with no other studied variables being relevant. Our results are consistent with other studies that advocate for the benefits of using scales to identify the risk of falls [ 3 , 13 , 15 , 16 , 20 , 21 , 22 ]. Likewise, the systematic review by Miake-Lye et al [ 19 ] expresses the benefits of programs that include interventions to identify risk factors associated with falls in acute care environments.…”
Section: Discussionsupporting
confidence: 93%
“…Almost all studies on the incidence of falls that we reviewed were in agreement with the benefits of applying preventive measures based on the risk identified and/or illness [ 13 , 15 , 16 , 18 , 20 , 22 , 30 , 32 , 39 ]. A systematic review by Avanecean et al [ 35 ] indicated patient-centered interventions, in addition to tailored patient education, may have the potential to be effective in reducing fall rates in acute care hospitals.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…5 Combined grip strength (GS), WS, and one-leg standing balance is better in predicting all-cause mortality than single test. 6 Meanwhile, toward the effects of combined models on discriminating potential fallers, those models mostly included factors overriding multiple aspects to increase the reliability of assessment, like medical history, psychological condition, surrounding environment and functional tests, [7][8][9] thus lacking of an easy and convenient fallscreening tool based on functional tests only, making our study more valuable.…”
Section: Introductionmentioning
confidence: 99%
“…Paresthesia, due to peripheral neuropathy or sensorial loss, produces several sudden sensations, which in turn can decrease motor and spatial perceptions, which ultimately results in falls [20,21]. The overactive bladder is a strong predictor of falls in older adults, which is associated with the urgency of having to get to the restroom [4,[22][23][24]. Insomnia as well as the medication prescribed for sleep disorders are also associated with a risk of falls [24,25].…”
Section: Introductionmentioning
confidence: 99%